2015
DOI: 10.1007/s12035-015-9418-5
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Peripheral TNF-α and Downregulation of Microglial Activation by Alpha-Lipoic Acid and Etanercept Protect Rat Brain Against Ischemic Stroke

Abstract: Ischemic stroke, caused by obstruction of blood flow to the brain, would initiate microglia activation which contributes to neuronal damage. Therefore, inhibition of microglia-mediated neuroinflammation could be a therapeutic strategy for ischemic stroke. This study was aimed to elucidate the anti-inflammatory effects of alpha-lipoic acid and etanercept given either singly or in combination in rats subjected to middle cerebral artery occlusion. Both α-lipoic acid and etanercept markedly reduced cerebral infarc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 58 publications
3
36
0
Order By: Relevance
“…In the study of Wu et al [36], the neuroportective of α-LA was attributed to inhibition of peripheral tumor necrosis factor-alpha and downregulation of brain microglial activation. In another research, the effect of α-LA was partially attributed to activation of insulin receptor because HNMPA-(AM)3, an insulin receptor inhibitor, blocked the neurorestorative effects of α-LA [12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the study of Wu et al [36], the neuroportective of α-LA was attributed to inhibition of peripheral tumor necrosis factor-alpha and downregulation of brain microglial activation. In another research, the effect of α-LA was partially attributed to activation of insulin receptor because HNMPA-(AM)3, an insulin receptor inhibitor, blocked the neurorestorative effects of α-LA [12].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies about the regulation of lipoic acid on ischemic stroke have been reported in animal models [11, 12] and in clinical study [13]. The cellular and molecular mechanisms associated with the protective effects of LA in ischemic stroke are partially be attributed to downregulation of microglial activation [11] and activation of insulin receptor [12]. In addition, LA attenuates cardiomyoctyes necrosis and apoptosis by activating the PI3K/Akt pathway as well as subsequent Nrf2 and HO-1 in experimental animal models of myocardial ischemia [14].…”
Section: Introductionmentioning
confidence: 99%
“…As reviewed by Pan and Kastin (2007), TNF-α was shown to have both detrimental and beneficial effects in stroke [121]. Several studies reported that inhibition of TNF-α (e.g., by etanercept, a human TNFR2-IgG Fc fusion protein) reduces infarct size and neuroinflammation [122][123][124][125], while, on the other hand, complete knockout of both TNFRs increases the sensitivity for stroke and aggravates neuronal damage [5]. Moreover, in stroke in vitro and animal models, pre-treatment with TNF-α (which models ischemic preconditioning) mediates neuroprotective effects after ischemia [126,127].…”
Section: Ischemic Strokementioning
confidence: 99%
“…Moreover, it may be that certain compounds, in certain conditions, do not necessarily have to pass the BBB to reach therapeutic effects. For example, in rat MCAO models for cerebral ischemia beneficial effects were reported upon intraperitoneal injection of etanercept [124,125]. However, it may be that etanercept could enter the brain via disruptions in the BBB, induced by the MCAO [124].…”
Section: Targeting Tnfrs As Treatment For Neurodegenerative Disordersmentioning
confidence: 99%
See 1 more Smart Citation